Dichlorido(4-methoxy-2-{ 2-(piperazin-4-ium-1-yl)ethyl iminomethyl}pheno late)cadmium - Salga, M.S.; Khaledi, H.; Ali, Hapipah Mohd (International Union of Crystallography, 2011)
In the title compound, [CdCl2(C14H21N3O2)], the Schiff base ligand chelates the Cd-II ion in an N,N,O-tridentate fashion. Two Cl atoms complete a distorted square-pyramidal coordination environment around the metal atom. In the crystal, adjacent molecules are linked through C-H center dot center dot center dot pi interactions into infinite chains along the a axis. The molecules are further connected into a three-dimensional network via N-H center dot center dot center dot O, N-H center dot center dot center dot Cl and C-H center dot center dot center dot Cl interactions. The ethylene group is disordered over two sets of sites in a 0.520 (10):0.480 (10) ratio.